2022
DOI: 10.3390/nano12173057
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Growth of Ceria-Modified N-Doped Carbon-Based Materials and Their Performance in the Oxygen Reduction Reaction

Abstract: Owning to their distinctive electronic structure, rare-earth-based catalysts exhibit good performance in the oxygen reduction reaction (ORR) and can replace commercial Pt/C. In this study, CeO2-modified N-doped C-based materials were synthesized using salt template and high-temperature calcination methods, and the synthesis conditions were optimized. The successful synthesis of CeO2–CN–800 was confirmed through a series of characterization methods and electrochemical tests. The test results show that the mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Various types of ceramic combinations embedded in nickel-based coatings, such as Ni–La 2 O 3 –CeO 2 [30] and Ni–Bi 2 O 3 –CeO 2 [31], have been studied, and the results indicate a better enhancement effect than those reinforced by single-type ceramic particles. The rare earth oxide, cerium oxide (CeO 2 ), is an interesting ceramic material labelled with excellent anti-corrosion, wear resistance, catalytic activity, and good conductivity [30,32], and it has been used in MMCs for enhancement. Li et al [33] prepared Ni–W–ZrO 2 –CeO 2 nanocomposite protective coatings and found out that the combination of ZrO 2 and CeO 2 could obviously improve the hardness, wear, and corrosion resistance of the Ni-W matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of ceramic combinations embedded in nickel-based coatings, such as Ni–La 2 O 3 –CeO 2 [30] and Ni–Bi 2 O 3 –CeO 2 [31], have been studied, and the results indicate a better enhancement effect than those reinforced by single-type ceramic particles. The rare earth oxide, cerium oxide (CeO 2 ), is an interesting ceramic material labelled with excellent anti-corrosion, wear resistance, catalytic activity, and good conductivity [30,32], and it has been used in MMCs for enhancement. Li et al [33] prepared Ni–W–ZrO 2 –CeO 2 nanocomposite protective coatings and found out that the combination of ZrO 2 and CeO 2 could obviously improve the hardness, wear, and corrosion resistance of the Ni-W matrix.…”
Section: Introductionmentioning
confidence: 99%